Organic acid metabolism in Chinese dwarf cherry [Cerasus humilis (Bge.) Sok.] is controlled by a complex gene regulatory network - Guo, Caizhen; Wang, Pengfei; Zhang, Jiancheng; Guo, Xiwen; Mu, Xiaopeng; Du, Junjie (Frontiers in Plant Science, 2022)
The acidity of Chinese dwarf cherry (Cerasus humilis (Bge.) Sok.) fruits is a key factor affecting the sensory quality of fruits, and it undergoes great changes during development.The molecular mechanisms of these changes is still unclear.In this study, fruits of high-acid 'Nongda4' and low-acid 'DS-1' varieties of Chinese dwarf cherry were used to determine the acid content at different developmental stages. We used transcriptome profiles to identify key genes related to organic acid metabolism and construct their co-expression networks, and we studied the expression patterns of key genes in 36 Chinese dwarf cherry accessions. The titratable acid content of both 'DS-1' and 'Nongda4' fruits first increased and then decreased during fruit development; however, the titratable acid content of 'DS-1' fruits changed to a minor extent. The organic acid content of 'Nongda4' was significantly higher than that of 'DS-1'. The organic acids in mature fruits were mainly malic acid and citric acid. Analysis of the differentially expressed genes related to organic acid metabolism revealed six key genes, including two MDH genes, one tDT gene, one ME gene, one PEPCK gene, and one VHA gene. Weighted gene co-expression network association analysis revealed four modules that were significantly correlated with organic acid content, and 10 key genes with high connectivity among these four modules were screened, including two PK genes, two MDH genes, two ME genes, one PEPCK gene, one VHA gene, one PEPC gene, and one tDT gene. According to the expression patterns of genes in different Chinese dwarf cherry accessions, seven genes were confirmed to represent key genes related to the regulation of organic acids during Chinese dwarf cherry fruit development. These results provide a foundation for further studies on the molecular mechanism of organic acid accumulation in Chinese dwarf cherry fruit.